Recording And Valuation Of Inventory Trade Based On Sak EMKM - Dewata, Evada; Desmarani, Astri; Sandrayati (LPPM Universitas Timor, 2025)
Inventory recording applied by HJ Pharmacy is still simple, which only records the number of items without including the price per unit. In addition, inventory valuation has not used any method so that to find out the value of the company's final inventory, the company only calculates it by means of the purchase price of the last inventory multiplied by the number of units of final inventory. The purpose of this community service is to find out how to record and assess the inventory of trade goods based on SAK EMKM. The recording method uses the perpetual method and the valuation uses the FIFO and Average methods. Based on the results of the author's analysis, recording inventory of trade goods at the HJ Pharmacy can use the perpetual method because by using this method the company can easily record and know the amount and value of inventory at any time, without doing a physical count in the warehouse first. Meanwhile, the valuation of trade goods inventory at the HJ Pharmacy can use the FIFO method, because the gross profit obtained by the company is greater than using Average.